Multivalent metal ion hybrid capacitors: a review with a focus on zinc-ion hybrid capacitors. Issue 23 (7th May 2019) - Dong, Liubing; Yang, Wang; Yang, Wu; Li, Yang; Wu, Wenjian; Wang, Guoxiu
Abstract : Multivalent metal ion hybrid capacitors are overviewed from the angle of design concept, configuration, electrochemical behavior and energy storage mechanism. Abstract : Multivalent metal ion hybrid capacitors have been developed as novel electrochemical energy storage systems in recent years. They combine the advantages of multivalent metal ion batteries ( e.g., zinc-ion batteries, magnesium-ion batteries, and aluminum-ion batteries) with those of supercapacitors, and are characterized by good rate capability, high energy density, high power output and ultralong cycle life. Herein, after a brief introduction to supercapacitors and multivalent metal ion batteries, we reviewed the recent progress in research on multivalent metal ion hybrid capacitors, with a focus on zinc-ion hybrid capacitors, from the perspectives of design concept, configuration, electrochemical behavior and energy storage mechanism. An outlook of the future research regarding multivalent metal ion hybrid capacitors was also presented. This review will be beneficial for researchers around the world to have a better understanding of multivalent metal ion hybrid capacitors and develop novel electrochemical energy storage systems to meet the demands of rapidly developing electric vehicles and wearable/portable electronic products.